2009
DOI: 10.1016/j.theochem.2009.05.003
|View full text |Cite
|
Sign up to set email alerts
|

H2O2 adsorption on the ice Ih surface. Theoretical study with systematic assessment of the orientation isomerism of the hydrogen bond network

Abstract: a b s t r a c tSemiempirical (PM3) and DFT (B3LYP/6-31++G(d,p)) calculations of the structure and energies of the variety of water clusters modeling 4680 fragments of the ice surface with different topology of the hydrogen bond network have been performed in order to analyze the contributions of various orientational isomers into the energy distributions of clusters and their impact onto the adsorption ability relatively to the H 2 O 2 molecule. It was found that, in the framework of the considered model, only… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 29 publications
1
8
0
Order By: Relevance
“…Consequently, for the explanation of the results obtained we can assume that H 2 O molecules are retrieved within the bulk mainly as a result of H+OH recombination reaction that follows immediately after photodissociation of H 2 O, so that photoproducts do not have sufficient time to escape from the lattice site where they were born. However, directly at the surfaces of the ice particles the situation might be different due to different intermolecular hydrogen bonding interactions (Ignatov et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, for the explanation of the results obtained we can assume that H 2 O molecules are retrieved within the bulk mainly as a result of H+OH recombination reaction that follows immediately after photodissociation of H 2 O, so that photoproducts do not have sufficient time to escape from the lattice site where they were born. However, directly at the surfaces of the ice particles the situation might be different due to different intermolecular hydrogen bonding interactions (Ignatov et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…22,23 This model is simple for construction and calculation, provides the proper physical parameters both for slabs and clusters (e.g., dipole moment of the bulk ice is close to zero) and it was already successfully used previously in adsorption studies. 24 Because the changes in the surface proton ordering result in 10À15% of adsorption energy, 21 we consider this value as an intrinsic uncertainty of the model used here. The quantum chemical method used throughout the studies of the minimal clusters (H 2 O) 48 and (H 2 O) 56 was the density functional theory at the BLYP/6-31þþG(d,p) level.…”
Section: ' Surface Models and Theoretical Methodsmentioning
confidence: 99%
“…All of the structures have different adsorption ability and different contribution into the average adsorption energy of the bulk ice. Recently, we estimated the differences in the adsorption ability of the clusters with various proton ordering modeling the H 2 O 2 adsorption on a variety of different (random) proton-disordered structures of (H 2 O) 11 composition . The results obtained at the B3LYP/6-31++(d,p) level showed that the effect of different proton ordering on the H 2 O 2 adsorption energy is not very pronounced although it is noticeable.…”
Section: Surface Models and Theoretical Methodsmentioning
confidence: 99%
“…A relatively strong peak at $2850 cm À1 for solid H 2 O 2 is typically assigned to the n 2 + n 6 combination band; 33,50 however, some studies considered that this assignment is disputable. 51,52 Ignatov et al 51 proposed that this peak is attributable to an OH valence band of the H 2 O 2 molecule placed in the unusual surface environment. The present results imply that the peak intensity at $2850 cm À1 might correlate with the conguration of H 2 O 2 on the substrate.…”
Section: Dependence Of Reaction Efficiency On Temperature and Type Of...mentioning
confidence: 99%